2017
DOI: 10.1038/s41598-017-01992-x
|View full text |Cite
|
Sign up to set email alerts
|

Breed, sex, and litter effects in 2-month old puppies’ behaviour in a standardised open-field test

Abstract: A considerable number of studies have reported differences among dog breeds with respect to their genetic profile, cognitive abilities or personality traits. Each dog breed is normally treated as a homogeneous group, however, researchers have recently questioned whether the behavioural profile of modern breeds still reflects their historical function or if the intense divergent selective pressures and geographical barriers have created a more fragmented picture. The majority of studies attempting to assess and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…environmental, previous experience or human-animal interactions) play in determining the severity of the fear response. This mirrors findings reported in previous studies investigating neuter age and stranger-directed aggression [28] or fear-related behaviours [29], source of acquisition and non-social or stranger-directed fear [42], and litter size and personality [43].…”
Section: Other Contributing Factorssupporting
confidence: 88%
“…environmental, previous experience or human-animal interactions) play in determining the severity of the fear response. This mirrors findings reported in previous studies investigating neuter age and stranger-directed aggression [28] or fear-related behaviours [29], source of acquisition and non-social or stranger-directed fear [42], and litter size and personality [43].…”
Section: Other Contributing Factorssupporting
confidence: 88%
“…Within breed variation is commonly highlighted in the literature (Björnerfeldt et al 2008;Barnard et al 2017), including within breed variation for odour discrimination ability (Lazarowski et al 2015). Our results also demonstrated that individual variation was prominent in all breeds.…”
Section: Discussionsupporting
confidence: 77%
“…The large degree of individual variation within breeds, both during training and accuracy testing, was not anticipated. Previous studies have highlighted the degree of individual variation within breeds (Björnerfeldt et al 2008;Barnard et al 2017), including their odour discrimination ability (Lazarowski et al 2015). Due to this study's small sample size, however, broad conclusions cannot yet be drawn on specific dog breed's trainability or working suitability.…”
Section: Aim 3 -Breed Comparisonmentioning
confidence: 99%
“…A possible explanation for this could be the more rapid maturation of females over males of the same age [ 27 ]. However, gender was not discerned to play a role in approximately 300 puppies undergoing an open field test at the age of 8 weeks [ 28 ]. Nevertheless, responsiveness towards noise was not investigated in any of these three studies [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, gender was not discerned to play a role in approximately 300 puppies undergoing an open field test at the age of 8 weeks [ 28 ]. Nevertheless, responsiveness towards noise was not investigated in any of these three studies [ 26 28 ]. Therefore, the question remains if the potentially stronger response to sudden noise indicated for female puppies is attributable to differences in ontogenetic development.…”
Section: Discussionmentioning
confidence: 99%